Wood flour / ceramic reinforced Polylactic Acid based 3D - printed functionally grade structural material for integrated engineering applications: A numerical and experimental characteristic investigation - Thirugnanasamabandam, Arunkumar; Prabhu B., .; Mageswari, Varsha; Murugan V., .; Ramachandran, Karthikeyan; K., Kadirgama (KeAi Communications Co. Ltd, 2024)
Recently, efforts have been done to capitalize on the potential of multidisciplinary research in order to produce unique features in polymer technology. To improve its physical and chemical properties for any intended use, the most promising Polylactic acid (PLA) has recently been copolymerized using other polymeric or non-polymeric components. This investigation aims to employ the material extrusion (MEX) process to develop a new functionally grade structural material (FGSM) by alternate layer deposition of wood flour reinforced PLA (WPLA) and ceramic reinforced PLA (CPLA). The mechanical properties of the printed laminates are examined using tensile, compression and three point bend tests. The microscopic investigation is used to assess fracture morphologies. A numerical simulation is also performed using ABAQUS under standardized parametric settings to investigate the mechanical behaviour of the laminates. The experimental and numerical results are consistent, with a deviation about ∼1 %. The tensile, compressive, and flexural strength of the newly developed FGSM are 61.39, 95.4, and 107.8 % higher than those of WPLA printed laminates. Furthermore, the acquired mechanical behaviour results are merely comparable to those of CPLA printed laminates. DSC thermograms demonstrate that FGSM has a better glass transition temperature (66oC) and a cold crystalline temperature (87.63oC), which contributes to its thermal stability. Overall, the newly developed FGSM might be considered a viable alternative, mechanically strong, and less expensive polymer composite material for structural built applications in any engineering and related fields.